The Relationship Between Mother’s Knowledge and Breastfeeding Behavior at Mother and Child Hospital Ananda Makassar in 2022 - Muftihatul Jannah; Syatirah Jalaluddin; Fhirastika Annisha; Jelita Inayah Sari; Rahmi Damis5 (Lembaga Pengembangan Kinerja Dosen, 2025)
Breast milk is the most complete form of nutrition for infants, capable of fulfilling all their needs across physical, psychological, social, and even spiritual dimensions. It contains essential nutrients, antibodies, and bioactive components that support optimal growth and development while fostering emotional bonding between mother and child. A mother’s level of knowledge plays a pivotal role in shaping her motivation and commitment to breastfeeding, as informed mothers are more likely to initiate and maintain exclusive breastfeeding practices. This study aims to examine the relationship between maternal knowledge and breastfeeding behavior at Mother and Child Hospital (RSIA) Ananda Makassar in 2022. Employing a quantitative research approach with an analytical observational design, the study utilized a cross-sectional method to capture data at a single point in time. Research was conducted from December 2022 to January 2023, targeting a population of 329 mothers who delivered at RSIA Ananda Makassar between May and December 2022. Using purposive sampling based on specific inclusion criteria, a total of 112 respondents were selected for participation. Data were analyzed using the Chi-Square test to assess the association between the independent variable (maternal knowledge) and the dependent variable (breastfeeding behavior). A significance level of 5% (α = 0.05) was applied to determine statistical relevance. The results revealed a significant relationship between mothers’ knowledge levels and breastfeeding behavior (p = 0.003), indicating that higher knowledge levels were associated with better breastfeeding practices. These findings highlight the importance of health education interventions aimed at increasing maternal knowledge on breastfeeding. Strengthening awareness programs, providing counseling during antenatal and postnatal care, and involving family support systems could enhance breastfeeding behaviors. Ultimately, improving maternal knowledge serves as a key strategy to promote exclusive breastfeeding, which in turn contributes to improved infant health outcomes and the overall well-being of both mother and child.